Three Level Boost T-Type Inverter in Open-Circuit Fault of S1X Power Switch Condition - Trần Vĩnh Thanh; Nguyễn M Khai; Đỗ Đức Trí (Journal of Technical Education Science, 2024)
There are many pulse-width modulation (PWM) control techniques reported for three-level T-type inverter (3L-T2I) to address open-circuit fault (OCF) of half-bridge power switches. However, these conventional fault-tolerant (FT) strategies significantly increase voltage rating of capacitors in comparison with normal operation. This paper presents a new 3LBT2I-FT which can improve capacitor voltage rating compared to others. In this topology, a conventional three-level boost (3LB) converter combined with a normally closed relay is installed before 3L-T2I. In post-fault condition, the relay is opened, and the proposed inverter operates like a two-stage two-level inverter. Under this method, the faulty power switch operating state of inverter side is recovered by power switches of 3LB circuit and bi-directional power switches of 3L-T2I. In comparison with previous FT methods, the proposed FT method can improve voltage stress of capacitor by 50%. This advantage leads to decrease power switch voltage rating. The proposed topology/FT method are verified by PSIM software.